2023
DOI: 10.1002/jid.3779
|View full text |Cite
|
Sign up to set email alerts
|

Categorising households based on shock severity experience: The effects of remittances on consumption smoothing post‐shock in Nigeria

Abstract: Existing literature suggests that remittances can help households in developing countries cope with post‐shock consumption. Focusing on Nigeria, where remittance receipts reached $25B in 2018 with increasing incidences of shocks, this study puts this claim to the test by categorising households into two: the group that suffered the most severe shock types and the group that suffered less severe shock types. Data is sourced from the World Bank and linearised regression results indicate that remittances benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This steady growth in remittances has attracted considerable interest in the academic literature, which seeks to assess the extent of their effects on various economic and social aspects. Previous research has identified that remittances contribute to improving the stability of household consumption (Mondal and Khanam 2018;Otame 2023), reducing food insecurity (Mora-Rivera and van Gameren 2021), alleviating restrictions on access to financial resources (Fromentin 2017), promoting a more equitable distribution of income (Bang et al 2016), and, in general, improving the quality of life of remittance recipient families (Feld 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This steady growth in remittances has attracted considerable interest in the academic literature, which seeks to assess the extent of their effects on various economic and social aspects. Previous research has identified that remittances contribute to improving the stability of household consumption (Mondal and Khanam 2018;Otame 2023), reducing food insecurity (Mora-Rivera and van Gameren 2021), alleviating restrictions on access to financial resources (Fromentin 2017), promoting a more equitable distribution of income (Bang et al 2016), and, in general, improving the quality of life of remittance recipient families (Feld 2022).…”
Section: Introductionmentioning
confidence: 99%